XAFKINTU. RECOVERING OUR ECONOMIC SYSTEM. BUILDING A NEW PROPOSAL - Anchio Boroa, Claura (Revista de Historia Social y de las Mentalidades, 2014)
This article aims to provide some thoughts on  the use of Xafkintu, Mapuche form of economic  exchange, establishing crossings with history  and present days as an instance to think about  this practice nowadays within a Mapuche  economic development project. All this is seen  from an intraethnic or emic perspective, and  pointing to new challenges within the Mapuche  movement.
Keywords: Xafkintu; Economic development; Mapuche